Water productivity in direct seeded rice and puddled transplanted rice: Evidence from farmers’ practices - Deb, Proloy; Urfels, Anton; Kumar, Virender; Dubey, Swatantra Kumar; Singh, Jasbir (CGIAR, 2024)
Research carried out by the International Rice Research Institute in northwestern India reveals that planting direct seeded rice increases water productivity and reduces energy demands